SANITATION AND DETOXIFICATION OF ALPACA (VICUGNA PACOS) MEAT WITH SARCOCYSTIOSIS THROUGH SMOKED AND CURED - Vilca L., Miguel (2013)
Hot and cold smoked, dry and wet cured, wet-cured and smoked, and dry-cure and smoked techniques for sanitation and detoxification of alpaca meat naturally infected with macrocysts of Sarcocystis aucheniae were evaluated. Eighteen puppies of 4-6 months of age were fed with the infected and treated alpaca meat (100 macrocysts per puppy). Lysates of macrocysts from treated meats were prepared and inoculated into 18 rabbits (100 μ/kg of body weight, subcutaneously). Furthermore, lysates were boiled (100º C for 10 min) and inoculated into 8 rabbits. Only dogs of the positive control group and the wet cured group eliminated sporocysts after 15 days of ingestion. None of the treatments were able to detoxify alpaca meat infected and rabbits died within 12-27 h post- inoculation of lysates. The heat treatment denatured macrocysts lysates protein and none of the rabbits die after inoculation.